2018
DOI: 10.1364/oe.26.030162
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning guided rapid focusing with sensor-less aberration corrections

Abstract: Non-invasive, real-time imaging and deep focus into tissue are in high demand in biomedical research. However, the aberration that is introduced by the refractive index inhomogeneity of biological tissue hinders the way forward. A rapid focusing with sensorless aberration corrections, based on machine learning, is demonstrated in this paper. The proposed method applies the Convolutional Neural Network (CNN), which can rapidly calculate the low-order aberrations from the point spread function images with Zernik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…Over the last years, deep learning-based approaches using convolutional neural networks (CNNs) have proven to be powerful and computationally efficient for image-based classification and regression tasks for microscopy images [18,19]. Recently, several studies demonstrated that deep learning-based phase retrieval can produce accurate results at fast processing speeds [20][21][22][23][24][25], however they fall short regarding their practical applicability. Some of these approaches [22][23][24] used purely simulated synthetic data, where generalizability to real microscopy images is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last years, deep learning-based approaches using convolutional neural networks (CNNs) have proven to be powerful and computationally efficient for image-based classification and regression tasks for microscopy images [18,19]. Recently, several studies demonstrated that deep learning-based phase retrieval can produce accurate results at fast processing speeds [20][21][22][23][24][25], however they fall short regarding their practical applicability. Some of these approaches [22][23][24] used purely simulated synthetic data, where generalizability to real microscopy images is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these approaches [22][23][24] used purely simulated synthetic data, where generalizability to real microscopy images is unclear. Others focused on specific microscopy acquisition modes (such as using biplanar PSFs [20]) or microscopy setups that allow to collect large sets of experimental ground truth data for training and prediction [21,25], thus limiting this approach in practice. Moreover, most studies lack comparison against strong classical phase retrieval methods that are used in practice.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning offers novel approaches to correct for aberrations encountered when imaging though scattering materials, [1][2][3][4] from astronomy [5][6][7][8][9] to microscopy with transmitted (for example [10][11][12]) and reflected light [13]. To find aberration corrections in these situations, machine learning typically relies on large synthetic datasets.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, training datasets are often based on combinations of Zernike polynomials [5][6][7][8][9][10][11][12][13] which might however not accurately capture all aspects of experimentally encountered aberrations. Additionally, for more strongly scattering samples, which require increasingly higher orders of Zernike modes, covering all potential scattering situations by sampling a sufficient number of different mode combinations eventually results in very large datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, adaptive optics (AO) is used to correct the wavefront aberrations, taking advantages of an active element such as a deformable mirror or a SLM . Nowadays, several methods based on AO were reported to successfully correct the phase patterns for doughnut beams.…”
Section: Introductionmentioning
confidence: 99%